Improving Teacher Competence Through GASING Method Training on Multiplication Material: A Mixed Methods Study - Tionomi Sihite; Siti Fatimah; Jarnawi Afgani Dahlan (FKIP - Universitas Riau, 2026)
Low mastery of multiplication concepts among teachers and students remains a challenge in Indonesian mathematics education. This study analyzed the effectiveness of the GASING Method (Gampang, Asyik, dan Menyenangkan / Easy, Fun, and Enjoyable) training in improving teacher competence in multiplication material and explored teachers’ experiences after the training. A mixed methods explanatory sequential design was employed. The quantitative sample comprised 46 teachers who participated in GASING Method training in Manokwari Regency, while the qualitative stage involved in-depth interviews with six teachers purposively selected based on N-Gain results. All participants achieved at least a medium N-Gain category. Therefore, three teachers with high N-Gain and three with medium N-Gain were interviewed. Data were analyzed using descriptive statistics, N-Gain analysis, Wilcoxon test, and thematic analysis. Results showed that average scores increased from 13.91 to 84.13, with a significant Wilcoxon difference (Z = -5.930, p < 0.001, r = 0.87) and a high average N-Gain value (0.83). Qualitative findings revealed improved conceptual understanding, strengthened pedagogical skills, and more positive attitudes toward mathematics learning. GASING Method training effectively improved teacher competence in multiplication material. However, findings from this single regency require examination in other educational contexts.